Safety and efficacy of Bonvital (Enterococcus faecium, DSM 7134) as an additive in water for drinking for sows. (28th February 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive Bonvital is a preparation of Enterococcus faecium authorised in feed for piglets and pigs for fattening, sows, chickens for fattening, chickens reared for laying and minor poultry species. The current authorisation in sows does not include the use of the additive in water for drinking. The additive is intended for use in water for drinking for sows at a minimum level of 2.5 × 10 8 colony forming unit (CFU)/L. This level is half of that minimum authorised in complete feed (5 × 10 8 CFU/kg), for the same target animals and would provide essentially the same exposure assuming that water consumption is approximately two‐ to three fold greater than feed consumption. Consequently, the conclusions on safety and efficacy of the additive when used in feedingstuffs also apply to its use in water for drinking for sows.